Bipolar Electro-Fenton System for Textile Dye Removal From Aqueous Solution - Somayyeh Dehghani; Abbas Rezaee; Fatemeh Hadadiyan (Iranian Journal of Health, Safety and Environment, 2017)
The main goal of this article is to study a bipolar electro-Fenton process using stainless steel mesh for removal of methylene blue (MB) as a model of textile dye from aqueous solution. The effect of operating parameters such as the applied current, supporting electrolyte, the type of electrode, H2O2 concentrations (1-10 mmol/L) and hydraulic retention time (5-60min) on the proposed electro-Fenton efficacy was evaluated. The optimum condition was obtained as follows: initial pH 3, the current density 1.4 mA/cm2, H2O2 10 mmol/L, Na2SO4 concentration 0.4 g/L as supporting electrolyte. The results show that the MB removal and COD reduction could be achieved 92% and 70%, respectively. The experimental results indicate that the bipolar electro-Fenton process using stainless steel mesh electrode is a promising wastewater treatment technique for removal of dye from aqueous solutions.